Quantum Computing and Applications: Its Effects on Cybersecurity - Quddus, Syed; Siddique, Saad Ali; Ramadan, Rabie A. (Transactions on Engineering and Computing Sciences, 2025)
Quantum computing is a developing field with the prospective to revolutionize the current advanced computing, it represents a fundamental shift from classical computing principles towards superposition, entanglement, and quantum interference, which are quantum mechanical principles. By using these distinctive principals and properties of quantum mechanics, ‘Quantum Computing’ processes information in the ways that are principally different from classical computers. This paper examines the fundamental concepts of quantum computing, its current and potential diverse applications, and the effects it has on cybersecurity. As quantum computing continues to advance, it proposes both forecasts and challenges, especially in cryptography, data protection, and security systems. This review paper focusses to discuss a comprehensive understanding of the junction between quantum computing and cybersecurity. It also point-outs the risks to current encryption theory and the new quantum-safe cryptography practices.